(15+9)x(22-5)=

Simple and best practice solution for (15+9)x(22-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15+9)x(22-5)= equation:


Simplifying
(15 + 9) * x(22 + -5) = 0

Combine like terms: 15 + 9 = 24
(24) * x(22 + -5) = 0

Combine like terms: 22 + -5 = 17
24x(17) = 0

Reorder the terms for easier multiplication:
24 * 17x = 0

Multiply 24 * 17
408x = 0

Solving
408x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '408'.
x = 0

Simplifying
x = 0

See similar equations:

| u/12-8=-8 | | 44=2(3.14) | | -8(t-4)-(t+1)=4 | | 6x-4=24x+2 | | 5(x+2)+7=17 | | r/2+6=5 | | 6(2x+33)+7(x+1)=u | | 3x^2+5=21 | | 50.2=2(3.14) | | 9(x-4)+4=-32 | | 12x-2=24x+7 | | 6(2x+30)+7(x+1)=u | | 10+(a+b)= | | -0.11(13x)= | | (2*7x)+(14+2x)*15=606 | | 3(8x+31)+5(x+1)=u | | 2x+7=X+1 | | 2*7x+14+2x*15=606 | | 2x+14+2x*15=606 | | -10(x-2)= | | 6=9x-8x+3 | | -9x-6y+3= | | 18p-3+7p+31= | | (13+a)+13= | | 0.80x+0.55(80)=0.40(100) | | y-12y= | | 12=m+2 | | 5(6x+35)+7(x+1)=u | | -2y+10=-2(2y+3) | | x-4=-13 | | 16x^2+y^2-16y=0 | | r+10=15 |

Equations solver categories